2019
DOI: 10.3390/ijms20246138
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Profiling of Resistant and Susceptible Sugarcane Cultivars in Response to Infection by Xanthomonas albilineans

Abstract: Sugarcane (Saccharum spp. hybrids) is a major source of sugar and renewable bioenergy crop worldwide and suffers serious yield losses due to many pathogen infections. Leaf scald caused by Xanthomonas albilineans is a major bacterial disease of sugarcane in most sugarcane-planting countries. The molecular mechanisms of resistance to leaf scald in this plant are, however, still unclear. We performed a comparative transcriptome analysis between resistant (LCP 85-384) and susceptible (ROC20) sugarcane cultivars in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…In the present study, the levels of gene transcripts encoding CTR1 were strongly increased, whereas those for genes encoding EIN2, EIN3, and ERF1 were decreased in both cultivars, suggesting that the ET signal transduction pathway plays negative roles in response to Aaa infection. Also, Ntambo et al revealed that this pathway was essential in sugarcane against X. albilineans [25] For auxin signal transduction pathways, we found that expression of genes for GH3 and a gene (Cluster-13677.452329) for SAUR was significantly upregulated in sugarcane, similar to a previous study upon sugarcane in response to X. albilineans infection [25]. Plants infected successfully by biotrophic pathogens show significant increases in IAA concentration and thereby upregulation of GH3 [60,61].…”
Section: Regulation Of Genes In Plant Hormone Signal Transduction Patsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, the levels of gene transcripts encoding CTR1 were strongly increased, whereas those for genes encoding EIN2, EIN3, and ERF1 were decreased in both cultivars, suggesting that the ET signal transduction pathway plays negative roles in response to Aaa infection. Also, Ntambo et al revealed that this pathway was essential in sugarcane against X. albilineans [25] For auxin signal transduction pathways, we found that expression of genes for GH3 and a gene (Cluster-13677.452329) for SAUR was significantly upregulated in sugarcane, similar to a previous study upon sugarcane in response to X. albilineans infection [25]. Plants infected successfully by biotrophic pathogens show significant increases in IAA concentration and thereby upregulation of GH3 [60,61].…”
Section: Regulation Of Genes In Plant Hormone Signal Transduction Patsupporting
confidence: 86%
“…Induction of many genes involved in photosynthesis and carbon metabolism, plant-pathogen interaction, plant hormone signal transduction, and phenylpropanoid biosynthesis was also observed. These metabolic process and defense-responsive pathways were also previously reported to be involved in responses of sugarcane to infection by diverse pathogens, further suggesting that these responses are largely conserved in sugarcane exposed to biotic stress [25,26,35].…”
Section: Overview Of Gene Transcription In Sugarcane During Aaa Infecmentioning
confidence: 53%
“…To check the reliability of our identified MAP kinase gene families, the genes were further confirmed in the S. spontaneum AP85‐441 genome (http://www.life.illinois.edu/ming/downloads/Spontaneum_genome/) and two publicly available published transcriptome datasets (PRJNA579959 and PRJNA549590) based on similarity >90% and high bit score (806–3578) with the R570 genome. The two transcriptome datasets originated from the sugarcane cultivars, ROC22 (resistant to red stipe) vs MT11‐610 (susceptible to red stipe) (Chu et al 2020) as well as LCP 85–384 (resistant to leaf scald) vs ROC20 (susceptible to leaf scald) (Ntambo et al 2019), which were inoculated with the pathogenic bacteria Aaa and Xa , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The two RNA‐seq datasets published by our group, which are available in the NBCI Short Read Archive (SRA) database under BioProject accession number PRJNA579959 and PRJNA549590, were used to investigate expression patterns of MAP kinase family genes in sugarcane cultivars (Ntambo et al 2019, Chu et al 2020). A value for fragments per kilobase of transcript per million fragments mapped (FPKM) was calculated for each gene, and the log 2 (Fold Change) transformed values for each MAP kinase family gene were used to generate a heatmap.…”
Section: Methodsmentioning
confidence: 99%
“…coeruleum or Ralstonia solanacearum in N. benthamiana [38]. More recently, most of WRKY33 alleles were significantly upregulated in sugarcane against the Xanthomonas albilineans attacks [54]. Collectively, WRKY TFs through self-regulation or hormones mediated signal transduction pathways proved to be effective for alleviating the infection stress caused by biotic or abiotic agents.…”
Section: Function and Expression Pattern Of Wrky Genes Under Biotic Smentioning
confidence: 99%